Short Communication: Tidal swamp rice cultivars of South Kalimantan Province, Indonesia: A case study of diversity and local culture - DINDIN HIDAYATUL MURSYIDIN; YUDHI AHMAD NAZARI; BUDI SETIADI DARYONO (Society for Indonesian Biodiversity, 2017)
Abstract. Mursyidin DH, Nazari YA, Daryono BS.2017. Tidal swamp rice cultivars of South Kalimantan Province, Indonesia: A case study of diversity and local culture.Biodiversitas 18: 427-432.Traditional rice (Oryza sativa L.) cultivars may become an indispensable part of the local culture and traditions of rice-growing people across Asia over many generations. The existence of this germplasm in the tidal swamp area of South Kalimantan Province, Indonesia has been observed morphologically and showed a close relationship with the local culture. A total of forty (40) traditional rice cultivars with different morphological characteristics have been found in this country, and still preserved sustainable by the local farmers along with their local culture and traditions. The tradition of 'wadai 41' may become a good example for this relationship. In this tradition, some traditional foods are made by the local people and use some of the local rice as basic ingredients. This information may be useful as guidance for conservation and rice breeding programs in the future. Keywords: Oryza sativa, genetic diversity, traditional cultivar, local culture, tidal swamp area